2005
DOI: 10.1007/s10815-005-4926-2
|View full text |Cite
|
Sign up to set email alerts
|

Is it worthwhile to operate on subclinical right varicocele in patients with grade II–III varicocele in the left testicle?

Abstract: Purpose : To determine whether repair of subclinical varicoceles in the right testicle results in significant seminal improvement in patients with clinical left varicocele. Methods : Patients were divided into two groups: Group I (unilateral varicocelectomy) and Group II (bilateral varicocelectomy-subclinical left varicocele). The mean sperm concentration before treatment was higher in Group I (21.01 ± 19.1) compared to Group II (5.7 ± 10.7) (p = 0.04). Results : An increase in volume was detected in the left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 37 publications
2
29
0
2
Order By: Relevance
“…The progressive rather than static effect of a varicocele upon male infertility suggests that, over time, the presence of a subclinical varicocele may result in abnormalities in the semen analysis and subsequently infertility (24). Therefore, the reported results in the present study are found to be in agreement with earlier ones (2,25,26), because we showed a significant improvement in different semen parameters and pregnancy rate after bilateral varicocelectomy in patients with clinical left and subclinical right varicoceles compared with left varicocelectomy alone for such patients. Meanwhile, Dhabuwala et al (2) showed that fertility was improved after subclinical varicocele ligation or immbolization.…”
supporting
confidence: 91%
“…The progressive rather than static effect of a varicocele upon male infertility suggests that, over time, the presence of a subclinical varicocele may result in abnormalities in the semen analysis and subsequently infertility (24). Therefore, the reported results in the present study are found to be in agreement with earlier ones (2,25,26), because we showed a significant improvement in different semen parameters and pregnancy rate after bilateral varicocelectomy in patients with clinical left and subclinical right varicoceles compared with left varicocelectomy alone for such patients. Meanwhile, Dhabuwala et al (2) showed that fertility was improved after subclinical varicocele ligation or immbolization.…”
supporting
confidence: 91%
“…These procedures can be performed immediately without the additional placement of a port and without requiring position changes. Scherr et al [23] and Pasqualotto et al [24] recommended bilateral varicocelectomies, because even small, subclinical, unrepaired varicoceles continue to have detrimental effects on bilateral testis function in patients with grade II-III left varicoceles. Recently, Park et al reported surgical outcomes of LESS-VL that included less pain than open inguinal varicocelectomy in cases of bilateral disease [10].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of left clinical and right subclinical varicoceles, it has been reported that bilateral varicocele ligation is effective. [21][22][23][24] Pasqualotto et al 21 said that even a small, subclinical unrepaired varicocele continues to have a detrimental effect on bilateral testis function in a patient with a grade II-III left varicocele. In addition, the greater improvement in semen parameters and pregnancy outcome associated with bilateral varicocelectomy support the concept of a detrimental dose-effect of varicoceles on male fertility potential.…”
Section: Discussionmentioning
confidence: 99%